Licoisoflavone B and glabridin from Glycyrrhiza glabra as potent nucleoprotein antagonists of Lassa virus: insights from molecular docking, dynamics simulation, PCA, and DFT studies - Sk. Faisal Ahmed; Md. Masudur Rahman Munna; Md. Hossain Ahmed; Md. Mostafizur Rahman; Minhajul Islam; Esha Mony Bristy (Journal of Genetic Engineering and Biotechnology)
Lassa virus causes a severe hemorrhagic disease referred to as Lassa fever. It exhibits a significant mortality rate among people in West and Central Africa. Currently, there is no vaccine available, and ribavirin is the sole treatment option with significant limitations. Given the lack of an effective medication, this study explores bioactive phytocompounds from the plant Glycyrrhiza glabra that may be safer and more effective than ribavirin in combating viruses’ nucleoprotein activity, which is essential for the replication of viruses and host immune evasion. Our virtual screening and multi-stage molecular docking analyses of 69 natural phytochemicals from this plant revealed the compounds licoisoflavone B and glabridin as potential therapeutics. These compounds exhibit strong binding affinities toward the target protein, with superior ADMET profiles. Both compounds also maintained structural stability throughout 100 ns molecular dynamics simulations, while principal component analysis further corroborated their conformational stability, highlighting potential efficiency. Furthermore, density functional theory analysis indicated favorable electronic properties, supporting the compounds’ potential as viable drug candidates. These findings suggested licoisoflavone B and glabridin as potential therapeutic candidates for Lassa fever. However, this study underscores the urgency of further experimental validation to advance these compounds toward novel anti-Lassa virus therapeutics.